(untitled) (Veterinary Science, 2021)
Species of the genus Chlamydia may infect various human and animal epithelia, causing diseases of varying severity, some of zoonotic transmission, and losses in food production. Psittacosis is a zoonosis caused by Chlamydia psittaci and has been widely studied. Although the presence of this species in breeding animals is not new, in recent years the search for and reporting of different species of chlamydia, especially in birds, has increased. This review article aims to provide an update on the Chlamydia species involved in avian infections, their taxonomic classification, prevalence in the world, and zoonotic and productive importance